Transculturação e poder em Zoé Valdés e Marilene Felinto : o pluralismo na construção identitária latino-americana - Nascif, Rose Mary Abrão (2008)
This work assumes that there is an equivalence between the subaltern condition of the woman and the Latin American continent, so that we intend to evaluate in which terms the novels La nada cotidiana and La hija del embajador , by the Cuban writer Zoé Valdés, and As mulheres de Tijucopapo , O lago encantado de Grongonzo and Obsceno abandono amor e perda , by the Brazilian writer Marilene Felinto, represent a favored microcosm on which one can observe the articulations of a patriarchal power (as a woman oppressor) and a metropolitan power (as a periphery oppressor). We intended to deal with the disagreements and agreements between the two writers, from a transcultural perspective as a meeting between central and peripherical cultures encouraged by the geopolitical displacement of intellectuals and artists -, and from the point of view of the power as an instrument of repression and exclusion. We detached the Spanish American and Brazilian literary outputs thoughout the 80 s and the 90 s, when the most of the feminine writings still remains marginalized by the canonical patterns. On the other hand, we emphasized the process of recognition and fragmentation provoked by the rupture/rescue of the memory, in which the main characters intend to take charge of their own lives by challenging the current establishment so that they could act as an active subject for the construction of the Latin American identities.